Indonesia : Ninth Review Under the Extended Arrangement. (IMF Staff Country Reports; Country Report, 2003)
The Indonesian authorities are to be commended for their continued strong policy performance under their arrangement with the IMF. The economy is sustaining steady growth despite a number of external and domestic shocks; inflation has continued to decline; and there has been an additional buildup of international reserves. Indonesia's fiscal policy remains geared toward achieving a significant fiscal consolidation and reduction in public debt. Progress has also been made in structural areas. The authorities are also encouraged to keep up the momentum of the privatization program.